From product-sales models to digital ecosystems and open science: The case of scholarly journal publishers in a small language country - Gudinavičius, Arūnas (Septentrio Conference Series, 2023)
Watch VIDEO.Scholarly publishers in small language countries face unique challenges, such as limited funding and resources, lack of visibility and recognition, and the dominance of international commercial publishers in the global academic publishing market. Therefore, understanding the role of publishers in promoting scholarly research in small language countries is crucial. This research aims to evaluate the publication of scholarly journals in a small language country (Lithuania) by analyzing the owners and publishers of scholarly journals. After collecting information about all scholarly journals published in 2020, a list of publishers and owners was compiled. The results show that since 1990, the publishing of Lithuanian scholarly journals has grown significantly: 225 scholarly journals were published in Lithuania, by 73 different publishers, in 2020. Social publishers, mostly state-funded universities, scientific institutes, colleges, still had the largest market share of scholarly periodicals, but commercial publishers also appeared and started to make a business out of publishing scholarly journals. Judging by the number of published articles, the five largest Lithuanian social publishers – state universities – published almost half of all scholarly articles published by Lithuanian publishers. Journals of social science were published the most, and one in five journals published in Lithuania applied relatively small publication fees. The analyzed data on publishers show that Lithuanian publishers have tried to take over and reorganize a number of scholarly journals from the Soviet era, while adapting to the dynamically changing world of scholarly publishing, and moving from simple product-sales models of the 20th century to new digital ecosystems of the 21st century, in which the essential distribution of publications is carried out digitally. The emerging diversity of publishers, the relatively moderate application of publication fees, and the growth in the number of articles show that Lithuanian publishers are quite well prepared for further challenges – the implementation of the European Science Foundation Plan S recommendations.
Keywords: scholarly publishers; scholarly journals; publishing; article processing charge; APC